Prodrug Systems (I): Lipid-based Doxorubicin Prodrugs and their nanodelivery systems - Olim, Filipe (2020)
Using natural lipids to covalently connect with antitumor agents to construct lipid-based molecular prodrugs and their nanosystems is a promising research frontier for sustainable medicinal chemistry, nanobiotechnology and tumor chemotherapy. This paper reviewed recent progress of lipid-based doxorubicin (molecular) prodrugs and their nanodelivery systems, including lipid-doxorubicin prodrugs, stimuli-responsive lipid-doxorubicin prodrugs, and lipid-doxorubicin prodrug-based drug co-delivery nanosystems. Additionally, possible future research outlooks in this field were also discussed.